Are founder-CEOs resilient to crises? The impact of founder-CEO succession on new firm survival. (March 2022) - Honjo, Yuji; Kato, Masatoshi
This article explores whether new firms managed by founder-chief executive officers (CEOs) are more likely to survive than those managed by successor-CEOs in times of crisis. Drawing on the concept of 'resilience' to adversity, we argue that founder-CEOs increase the likelihood of new firm survival, especially in times of crisis. Using a sample of Japanese firms founded during the 2003–2010 period, we examine the impact of founder-CEO succession on new firm survival. The analysis shows that new firms managed by founder-CEOs are less likely to liquidate than those managed by successor-CEOs, especially during the 2008–2009 financial crisis. This suggests that founder-CEOs are more resilient to crises than successor-CEOs. In contrast, new firms managed by successor-CEOs are more likely to exit via merger than those managed by founder-CEOs, regardless of macroeconomic conditions. These findings are robust after controlling for the endogeneity of CEO succession.